The wall and the garden : selected Massachusetts election sermons, 1670-1775 - Plumstead, A. W. (Arthur William), 1933- (University of Minnesota Press, 1968)
The election day sermon in colonial New England was an annual, formal address by a minister of the gospel to the newly assembled legislature of the colony. The tradition began in the Massachusetts Bay colony in 1634, and it continued, in Boston, for 250 y.